A Study on Manufacturing of Flange Joint Used in Transportation Vehicle - Harsh Kumar Sharma (AG Volumes, 2021)
Flange and flange connecting it to a commercial vehicle are processed in this investigation. Assemblies of Companion Flanges and Universal Drive shafts are also available. When the flange was brought in use in the commercial vehicles, it was seen that because if heavy friction, the part is deteriorating. To prevent this issue, a design was made which was further manufactured for accomplishing the goals of this study. When the product was ready, it was tested on CMM machine to find any type of error between the designed and manufactured product. The outcome obtained from the CMM machine showed a very small percentage of error. The new manufactured product had comparatively less amount of friction loss.